Multiscale molecular dynamics to investigate sodium ion channel oligomerisation - Glass, WG (2019)
Electrical signalling is key to a vast number of biological processes within the nervous system. For this to occur, specific types of transmembrane proteins, named voltage-gated ion channels, are utilised. In voltage-gated sodium (Nav) channels, recent advances in structural biology are beginning to solve structures in complex with so-called “auxiliary” β subunits. These transmembrane proteins are multifunctional and interact with the main α subunit of the Nav channel, in addition to having a cell adhesion function through their extracellular immunoglobulin (Ig) domain. In Nav1.5, β3 has been found to cross-link subunits within the membrane, as well as form trimers and higher order oligomers.